Terminology of Justice in the Quran On the Dimensions of Constitutional Law - Rohmah, Siti Ngainnur; Yunus, Nur Rohim (UIN Jakarta, 2024)
The Quran places great importance on justice, which significantly influences the development of constitutional Law. The Quran offers a thorough and inclusive explanation of justice language, encompassing individual and social dimensions. This essay seeks to examine the terminology of justice found in the Quran and its potential application within constitutional Law. Amidst the growing trend of globalization, it is crucial to comprehensively comprehend how the principles of justice outlined in the Quran can be effectively incorporated into constitutional legislation. This essay emphasizes the significance of incorporating Islamic principles into constitutional Law to establish a fair and enduring society.